2011
DOI: 10.1111/j.1474-9726.2011.00676.x
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of p21Cip1/Waf1 enhances proliferation, the expression of stemness markers, and osteogenic potential in human mesenchymal stem cells

Abstract: SummaryMammalian aging of many tissues is associated with a decline in the replicative and functional capacity of somatic stem cells. Understanding the basis of this decline is a major goal of aging research. Human bone marrow-derived multipotent stromal cells (MSCs) have been applied in the treatment of fracture nonunion. Clinical application of MSCs requires abundant cells that can be overcome by ex vivo expansion of cells, but often at the expense of stemness and differentiation potentiality. We first demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
73
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(83 citation statements)
references
References 44 publications
9
73
1
Order By: Relevance
“…Previous animal studies have implicated p21 (CIP1/WAF1) in tissue repair/regeneration, with p21 deficient mice being able to repair significant trauma to appendages without scarring . Furthermore, at least two studies by independent labs have shown that mesenchymal stem cells deficient in p21 expression have increased potential to differentiate into both adipocytes and osteoblasts (Yew et al, 2011;Cheng et al, 2011). Additionally, the recent study by Yew et al (2011) suggested that p21 levels fluctuated in bone marrow MSCs collected from different patients.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Previous animal studies have implicated p21 (CIP1/WAF1) in tissue repair/regeneration, with p21 deficient mice being able to repair significant trauma to appendages without scarring . Furthermore, at least two studies by independent labs have shown that mesenchymal stem cells deficient in p21 expression have increased potential to differentiate into both adipocytes and osteoblasts (Yew et al, 2011;Cheng et al, 2011). Additionally, the recent study by Yew et al (2011) suggested that p21 levels fluctuated in bone marrow MSCs collected from different patients.…”
Section: Discussionmentioning
confidence: 95%
“…1D). Since it had been previously reported that p21 levels in MSC populations correlated with osteogenic and adipogenic differentiation capacity (Yew et al, 2011), we next examined if the levels of p21 in the undifferentiated synovial MPCs was related to the chondrogenic differentiation capacity of the cells.…”
Section: P21 Expression In Undifferentiated Human Synovial Mpcsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings that altering p21 levels affects the expansion rates and GAG production of iPSC-derived chondrocytes are consistent with previous results in human MSCs showing that reduced p21 expression through the use of hypoxia, growth factors, or siRNA can increase both proliferative and differentiation potential. 24,25,38 An important result of p21 silencing was attenuation of the sharp decrease in cell number associated with early stages of pellet culture in control cells, a phenomenon that also occurs in other cell types. 29 BrdU staining indicated that increased DNA synthesis was one factor in the higher DNA content of pellets from p5 p21sh cells compared with controls, but silencing p21 may also have played a role in Images representative of pellets from two independent cell preparations.…”
Section: Discussionmentioning
confidence: 99%
“…The double-stranded DNA was inserted into the EcoRI and XhoI sites of the pMSCV-puro-miR30 vector. The following gene-specific sequences were used successfully: WWP1, 5Ј-GAGTTGATGATCGTAGAAG-3Ј (11); p21 Cip1 , 5Ј-GACAGATTTCTATCACTCCAA-3Ј (22). For transient transfection, HeLa cells at 70 -80% confluence were transfected with Lipofectamine 2000 (Invitrogen) following the manufacturer's instructions.…”
Section: Deletions In P27mentioning
confidence: 99%